2018
DOI: 10.3390/coatings8070238
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Plasma Monitoring of PECVD nc-Si:H Films and the Influence of Dilution Ratio on Structural Evolution

Abstract: We report plasma-enhanced chemical vapor deposition (PECVD) hydrogenated nano-crystalline silicon (nc-Si:H) thin films. In particular, the effect of hydrogen dilution ratio (R = H 2 /SiH 4) on structural and optical evolutions of the deposited nc-Si:H films were systematically investigated including Raman spectroscopy, Fourier-transform infrared spectroscopy (FTIR) and low angle X-ray diffraction spectroscopy (XRD). Measurement results revealed that the nc-Si:H structural evolution, primarily the transition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Furthermore, the various tuning algorithms from the matching box were considered to be highly classified and patented technology. A previous study also demonstrated that both the crystallization rate index (Hα*/SiH*) and the electron temperature (Si*/SiH*) increase in proportion to the increase of the dilution ratio [14]. Furthermore, quadruple mass spectra (QMS)-measured results indicated the radicals SiH x (0 < x < 4) reached various critical points of relative densities since the dilution ratio changes due to the different depletion level of silane radicals [14].…”
Section: Optical Emission Spectra Spectroscopy Analysismentioning
confidence: 85%
See 4 more Smart Citations
“…Furthermore, the various tuning algorithms from the matching box were considered to be highly classified and patented technology. A previous study also demonstrated that both the crystallization rate index (Hα*/SiH*) and the electron temperature (Si*/SiH*) increase in proportion to the increase of the dilution ratio [14]. Furthermore, quadruple mass spectra (QMS)-measured results indicated the radicals SiH x (0 < x < 4) reached various critical points of relative densities since the dilution ratio changes due to the different depletion level of silane radicals [14].…”
Section: Optical Emission Spectra Spectroscopy Analysismentioning
confidence: 85%
“…Silane (SiH 4 ) was used. The substrate temperature was fixed at~210 • C. The detailed processing parameters can be listed as follows: power 100 W; pressure 300 mTorr; source gas: SiH 4 , H 2 , and Ar; SiH 4 gas-flow 5 sccm; Ar gas-flow 3 sccm; H 2 gas-flow can be varied as 25, 50, 100, 150, or 200 sccm; deposition time 60 min; electrode distance 25 mm; and substrate temperature 210 • C. Hydrogen dilution ratio is defined as the ratio between the hydrogen flow-rate divided by the silane flow-rate (R = H 2 /SiH 4 ), which is the same definition as investigated previously in PECVD nc-Si:H films [14]. The substrate of CZ(100) n-type single-side polished wafer was used for all the experiments.…”
Section: Film Preparationmentioning
confidence: 99%
See 3 more Smart Citations